Differential Antifungal Activity of Human and Cryptococcal Melanins with Structural Discrepancies - Correa, Néstor; Covarrubias, Cristian; Rodas, Paula I.; Hermosilla, Germán; Olate, Verónica R.; Valdés, Cristián; Meyer, Wieland; Magne, Fabien; Tapia, Cecilia V. (Frontiers in Microbiology, 2017)
Melanin is a pigment found in all biological kingdoms, and plays a key role in protection against ultraviolet radiation, oxidizing agents and ionizing radiation damage. Melanin exerts an antimicrobial activity against bacteria, fungi and parasites. We demonstrated an antifungal activity of synthetic and human melanin against Candida sp. The members of the Cryptococcus neoformans and C. gattii species complexes are capsulated yeasts, which cause cryptococcosis. For both species melanin is an important virulence factor. To evaluate if cryptococcal and human melanins have antifungal activity against Cryptococcus species they both were assayed for their antifungal properties and physico-chemical characters. Melanin extracts from human hair and different strains of C. neoformans (n=4) and C. gattii (n=4) were investigated. The following minimun inhibitory concentrations (MICs) were found for different melanins against C. neoformans and C. gattii were (average / range): 13.7 / (7.8 – 15.6) and 19.5 / (15.6-31.2) µg/mL respectively, for human melanin; 273.4 / (125->500) and 367.2 / (125.5->500) µg/mL for C. neoformans melanin and 125 / (62.5-250) and 156.2 / (62-250) µg/mL for C. gattii melanin. Using Scanning Electron Microscopy (SEM) we observed that human melanin showed a compact conformation and cryptococcal melanins exposed an amorphous conformation. Infrared spectroscopy (FTIR) showed some differences in the signals related to C-C bonds of the aromatic ring of the melanin monomers. High Performance Liquid Chromatography (HPLC) established differences in the chromatograms of fungal melanins extracts in comparison with human and synthetic melanin, particularly in the retention time of the main compound of fungal melanin extracts and also in the presence of minor unknown compounds. On the other hand, MALDI-TOF-MS analysis showed slight differences in the spectra, specifically the presence of a minor intensity ion in synthetic and human melanin, as well as in some fungal melanin extracts. We conclude that human melanin is more active than the two fungal melanins against Cryptococcus. Although some physico-chemical differences were found, they do not explain the differences in the antifungal activity against Cryptococcus of human and cryptococcal melanins. More detailed studies on the structure should be considered to associate structure and antifungal activity.